Manajemen Pemasaran Online melalui Penerapan Iklan secara Digital - Nazara, Niat Daniati; Ginting, Andi Lopa (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research discusses online marketing management through the application of digital advertising. With the rapid development of technology and increasing use of the internet, traditional marketing methods are increasingly shifting towards digital marketing. Digital marketing offers various advantages, such as the ability to reach a wider audience, more precise targeting, and more efficient costs. This research aims to identify effective strategies in online marketing and evaluate the impact of digital advertising on consumer behavior. The development of the internet is changing the way of doing business, including in the retail business where the business model utilizes digital services in the transaction process which is known as e-commerce. This research aims to examine how in online marketing to implement online advertising and realize consumer buying interest. This research also uses a descriptive survey method using a verification approach. The population in this research is Lazada consumers in the city of Bandung, with a sample of 96 customers. The findings show that the implementation of online advertising has a direct impact on purchasing interest on the Lazada site. This research concludes that online marketing management through the implementation of digital advertising is a crucial component in modern business strategy. Companies that adopt this approach well can gain a significant competitive advantage in an increasingly digitally connected marketplace.